Netrin-4 Promotes Glioblastoma Cell Proliferation through Integrin β4 Signaling - Yizhou Hu (Neoplasia: An International Journal for Oncology Research, 2012)
Netrin-4 is a laminin-related secreted molecule originally found to have roles in neuronal axon migration. Recent studies have indicated that netrin-4 also participates in the development of nonneural tissues and modulates tumor cell proliferation and tumor metastasis. Here we have explored the functions and molecular mechanisms of netrin-4 in glioblastoma multiforme. The suppression of netrin-4 expression in glioblastoma cell lines significantly reduced cell proliferation and motility and increased serum deprivation-induced apoptosis. Using tandem affinity purification combined with protein identification by mass spectrometry, we found that integrin β4 interacts with netrin-4 and that it mediates mitogenic effects as well as AKT and mammalian target of rapamycin phosphorylation induced by netrin-4. Interestingly, netrin-4 acted as an inhibitor of cell proliferation in integrin β4-silenced glioblastoma cells, and high concentrations of netrin-4 reduced cell proliferation. The negative effects of netrin-4 on proliferation were mediated by UNC5B. Analysis of more than 400 primary tumors from The Cancer Genome Atlas repository revealed that the expression of netrin-4 is significantly downregulated in glioblastoma and that the reduced expression is linked to poor patient survival time. The expression of integrin β4 is increased in glioblastoma, and it predicts poor patient survival time. Current results illustrate a novel mechanism for glioma progression, where glioma cells reduce netrin-4 expression to decrease its inhibitory effects. In parallel, the expression of integrin β4 is upregulated to sensitize the cells to low concentrations of netrin-4 for maintaining cell proliferation.